Studying structurally-mechanical characteristics suppositories with amlodipine - Fadi Al Zedan; V. V. Gladyshev; B. S. Burlaka (Zaporožskij Medicinskij Žurnal)
Rheological behaviour suppositories with amlodipine on lypofiles to a basis are studied and character of temperature effect on their structurally-mechanical properties is positioned. It is revealed that the temperature of carrying out of technological operations of homogenization and overflow suppositories 50-55ºС is optimum, providing necessary fluidity suppositories masses at hypodispersion in it reacting and aids.